Optimal NHS service delivery to care homes: a realist evaluation of the features and mechanisms that support effective working for the continuing care of older people in residential settings - Goodman, Claire; Davies, Sue L.; Gordon, Adam L.; Dening, Tom; Gage, Heather; Meyer, Julienne; Schneider, Justine M.; Bell, Brian; Jordan, Jake; Martin, Finbarr C.; Iliffe, Steve; Bowman, Clive; et al. (NIHR Health Technology Assessment Programme, 2017)
Background: Care homes are the institutional providers of long-term care for older people. The OPTIMAL study argued that it is probable that there are key activities within different models of health-care provision that are important for residents’ health care.